2nd World Forum on the Right to Energy Marrakech, 19–21 June 2004. (13th December 2005) - Clerc, Michel
Founded in 2000, Droit a L'energie SOS Futur (Right to Energy SOS Future) is an international nongovernmental organisation that has its head office in France. It is in special consultative status with the Economic and Social Council of the United Nations (ECOSOC). Its active members are legal personalities: 180 organisations (NGOs, national and international union organisations) from 60 countries distributed among four continents and representing close to 35 million members. Our objectives are: to assemble all those wishing to act for the recognition of the right to energy as a basic human right, for the sharing of energy resources, and for the protection of the global environment, to mobilise around extreme situations of energy destitution in the world, to initiate specific and constructive proposals in partnership with major international institutions, governments, and the key actors of global civil society.